2023
DOI: 10.1007/s00167-023-07317-y
|View full text |Cite
|
Sign up to set email alerts
|

Lateral–medial asymmetry of posterior tibial slope and small lateral tibial plateau articular surface depth are morphological factors of lateral meniscus posterior root tears in ACL-injured patients

Abstract: Purpose To investigate whether knee morphological features, patient characteristics, and intraoperative indings are associated with a lateral meniscus (LM) posterior root tear (LMPRT) in anterior cruciate ligament (ACL) injuries with the integrated data from two academic centres. Methods This retrospective study used registry data acquired prospectively at two academic centres. Patients with ACL reconstruction (ACLR) with LMPRT and no other LM injury were selected (LMPRT group) from each database. The control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…First, we investigated several anatomic factors reported in previous studies including the lateral and medial posterior tibial slope (LPTS and MPTS), the asymmetry of LMPTS, medial and lateral meniscal slope (MMS and, LMS) and medial femoral condyle (MFC). LPTS has been extensively inspected as a potential risk factor for non-contact ACL injuries [ 19 , 23 , 24 , 29 ], but few studies have assessed whether it is related to ramp lesions. A cross-sectional study has indicated that the LPTS and the asymmetry of LMPTS were risk factors for ramp lesions in ACL-injured knees [ 12 ], while another study reported no correlation between LPTS and ramp lesions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we investigated several anatomic factors reported in previous studies including the lateral and medial posterior tibial slope (LPTS and MPTS), the asymmetry of LMPTS, medial and lateral meniscal slope (MMS and, LMS) and medial femoral condyle (MFC). LPTS has been extensively inspected as a potential risk factor for non-contact ACL injuries [ 19 , 23 , 24 , 29 ], but few studies have assessed whether it is related to ramp lesions. A cross-sectional study has indicated that the LPTS and the asymmetry of LMPTS were risk factors for ramp lesions in ACL-injured knees [ 12 ], while another study reported no correlation between LPTS and ramp lesions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the ACL ruptures, the compressive forces result in an anteriorly directed shear force, eventually leading to anterior translation and internal rotation of the tibia, posterior rolling of the LFC, and anterior rolling of the MFC, relatively [ 2 , 29 , 35 , 36 ]. According to previous studies, a steeper LPTS and a higher asymmetry of LMPTS could further increase anterior translation and internal rotation of the tibia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations